Uterine Hyperplasia Causes, Symptoms Consequences and Principles of Treatment - og‘li, Abdullo Akramov Axmad; oʻgʻli, Raxmatov Jasurbek Xurshid; qizi, Uroqova Marjona Shamsiddin; o'g'li, Isaqulov Ulug'bek Alisher; qizi, Ibrohimova Shahnoza Ilhom; Shuxratovich, Zairov Laziz (Journal of Medical Genetics and Clinical Biology, 2024)
In this article, the causes, symptoms, consequences, and treatment principles of Uterine Hyperplasia are described in detail, as well as an example of research conducted by world scientists.